Optimizing Apparent Metabolizable Energy and Digestible Amino Acids of Layer Feed by Response Surface Methodology - Widjaja, H.; Nahrowi; Jayanegara, A.; Utomo, D.; Hazen, K. (Faculty of Animal Science, IPB University, 2025)
Optimizing dietary energy and amino acid levels is essential for enhancing the performance and cost-efficiency of laying hens. The primary goals were to identify the optimal apparent metabolizable energy (AMEn) and digestible lysine (dLys) levels that maximize hen-day production (HDP) and egg weight (EW) while minimizing feed conversion ratio (FCR) and FC. A total of 150 cages, each housing five hens, were used. Hens with 24 weeks of age were assigned to ten dietary treatments following a central composite design (CCD), with AMEn levels ranging from 2,400 to 2,733 kcal/kg and dLys from 0.42% to 1.02%. The experiment was carried out during peak production (24 to 38 weeks of age). Response surface methodology (RSM) combined with CCD effectively optimized AMEn and dAA levels, providing practical insights for formulating cost-effective diets for commercial laying hens. Dietary dLys significantly influenced HDP and EW, while AMEn affected feed intake (FI). The optimal conditions, determined by the desirability function (DF), were AMEn of 2,660 kcal/kg and dLys of 0.81%, maximizing HDP and EW with minimal FCR and FC. Excluding EW from DF optimization, the best results were achieved at AMEn of 2,623 kcal/kg and dLys of 0.78%.